Performance Index and PSII Connectivity Under Drought and Contrasting Light Regimes in the CAM Orchid Phalaenopsis - Ceusters, Nathalie; Valcke, Roland; Frans, Mario; Claes, Johan E.; Van den Ende, Wim; Ceusters, Johan (Frontiers in Plant Science, 2019)
Crassulacean acid metabolism (CAM) is a specialized mode of photosynthesis characterized by improved water use efficiency mediated by major nocturnal CO2 fixation. Due to its inherent metabolic plasticity CAM represents a successful physiological strategy for plant adaptation to abiotic stress. The present study reports on the impact of drought stress and different light intensities (PPFD 50 and 200 µmol m-2 s-1) on the photosynthetic performance of the obligate CAM orchid Phalaenopsis ‘Edessa’ by integrating diel gas exchange patterns with assessments of the light reactions by analysing fast chlorophyll a fluorescence induction. Parameters such as PIabs (performance index), different energy fluxes per active reaction centre (RC) reflecting the electron flow from photosystem II to photosystem I and the energetic communication between PSII complexes defined as connectivity were considered fort the first time in a CAM plant. The performance index was identified as a very reliable and sensitive parameter to indicate the onset and progress of drought stress, and under restricted CO2 availability (due to closed stomata) leaves showed higher energy dissipation and partial inactivation of PSII reaction centres to reduce the energy input to the electron transport chain and as such aid in avoiding overexcitation and photodamage. Especially during CAM idling there is a discrepancy between continuous input of light energy but severely reduced availability of both water and CO2, which represents the ultimate electron acceptor. A higher PS II connectivity for plants grown under low light (p ~ 0.51) compared to plants grown under high light (p ~ 0.31) brought about similar specific energy fluxes of light absorbance, dissipation and processing through the electron transport chain, irrespective of the light treatment. With a 25% higher maximum quantum yield and comparable biomass formation, low light grown plants indeed proved to process light energy more efficiently compared to high light grown plants. Taken together, our results show a unique flexibility of CAM plants to optimise the light reactions under different environmental conditions in a dual way by either attenuating or increasing energy flux.